2009
DOI: 10.1111/j.1574-6968.2009.01758.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell death inStreptococcus mutans  biofilms: a link between CSP and extracellular DNA

Abstract: Streptococcal competence-stimulating peptides (CSPs) were once thought to passively communicate population density in a process known classically as quorum sensing. However, recent evidence has shown that these peptides may also be inducible ‘alarmones,’ capable of conveying sophisticated messages in a population including the induction of altruistic cellular suicide under stressful conditions. We have previously characterized the alarmone response in Streptococcus mutans, a cariogenic resident of the oral flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 30 publications
(42 reference statements)
3
110
0
2
Order By: Relevance
“…For example, in addition to killing bacterial competitors, bacteriocin production has been linked to biofilm formation through extracellular DNA release and autolysis (Perry et al, 2009a, b). Perry et al (2009a) showed that intracellular accumulation of unprocessed CipB (mutacin V) mediates autolysis and proposed that CipB may be involved in altruistic cell death of a subset of the population (fratricide) during stressful conditions. It is tempting to speculate that the unexpected enhanced survival of DclpP and DclpX during acid stress (Kajfasz et al, 2009) could, at least partially, be explained by a reduction in normal levels of mutacin V-mediated autolysis in these strains.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in addition to killing bacterial competitors, bacteriocin production has been linked to biofilm formation through extracellular DNA release and autolysis (Perry et al, 2009a, b). Perry et al (2009a) showed that intracellular accumulation of unprocessed CipB (mutacin V) mediates autolysis and proposed that CipB may be involved in altruistic cell death of a subset of the population (fratricide) during stressful conditions. It is tempting to speculate that the unexpected enhanced survival of DclpP and DclpX during acid stress (Kajfasz et al, 2009) could, at least partially, be explained by a reduction in normal levels of mutacin V-mediated autolysis in these strains.…”
Section: Discussionmentioning
confidence: 99%
“…The demand might often be coupled with a willingness or ability to contribute. In a stressful situation, lower reproductive potential may favor altruistic behavior, which at its extreme may cause some cells to commit suicide to the benefit of others (131). From an efficiency point of view, all these factors affect the actual need of the bacterial cells for the regulated target behavior, their potential or willingness to contribute to it, or the opportunity for the regulated behavior to be effective.…”
Section: Variability Of the Ai Production Rate: The Hybrid Push-pull mentioning
confidence: 99%
“…Recent data has shown a drastic reduction of XIP levels in the comX (r x ) deficient S. mutans strains, as it evidence the positive feed-back role of ComX in ComRS/XIP expression where its binding sites were localized either within or upstream of ComRS [38]. Earlier reports have also demonstrated that the increase in the concentration (2-4 lM) of CSP mediated cell-killing and growth arrest of S. mutans [39,40]. Likewise, the S. mutans on exposure to 10 lM of synthetic XIP (sXIP) has shown the killing effect, naturally score the phenomena of exploiting the pheromones (XIP) as a potent effector molecules to treat dental caries [41].…”
Section: S Mutans and Dental Cariesmentioning
confidence: 87%
“…The peptides were designed to have a targeted domain (8-aminoacid region of the CSP) fused with an antimicrobial peptide domain to show a robust species SigX (ComX) comR DNA transport, uptake and Recombination [12,36] ComAB nlmAB (comAB) Mutacin IV (bacteriocins), Maturation and export of CSP outside the cell [16,49] ComD comC/comD/comE (TCSTS) Class II bacteriocins and HK receptor for CSP signal [14,22] immA and immB (VicRK) comC Self-immunity proteins for protection from bacteriocins, acid tolerance [55] Lux S luxS Interspecies communication [39,40] Indian…”
Section: S Mutans and Dental Cariesmentioning
confidence: 99%